A Handbook of Bioethics Terms - Tubbs, James B. (Book collections on Project MUSE., 2009)
A valuable handbook of bioethics terms for undergraduate and graduate students in health care ethics, physicians, nurses, institutional ethics committees, and anyone interested in the health care field.